Acceptability and feasibility of Problem Management Plus to address mental health problems among remand prisoners in the Netherlands: a pilot randomised controlled trial protocol - Mathilde J. F. van Oudenaren; Anke B. Witteveen; Anja J. E. Dirkzwager; Marit Sijbrandij (Health & Justice)
Abstract Background Worldwide, the prevalence of mental health problems in prison populations is higher than in the general population. While prisons may provide opportunities to address mental health problems, the prison setting can also include obstacles to the actual delivery of interventions, such as mental health care staff deficiencies. A brief scalable psychological intervention such as the World Health Organization’s (WHO) Problem Management Plus (PM +) intervention, which is delivered by trained non-specialists, could be valuable in addressing common mental health problems in the prison setting. The primary aim of the study is to evaluate the feasibility and acceptability of PM + , adapted for use in Dutch remand prisons. The secondary aim is to examine barriers and facilitators for scaling up the adapted version of PM + in the Dutch prison setting. Method This single-blind pilot randomised controlled trial (RCT) will compare individual PM + with care-as-usual (PM + /CAU) to CAU only. Dutch-speaking remand prisoners (18 years or older; N = 60) who report an elevated level of psychological distress (K10 ≥ 16) will be included. The feasibility of the intervention will be reviewed using different measures such as recruitment success, intervention retention, protocol adherence, number of serious adverse events, and stakeholders' views. Participants will be assessed for self-reported anxiety, depression, self-identified problems, vulnerability for suicide and self-harm behaviour and post-traumatic stress disorder (PTSD) symptoms at baseline, one-week post-intervention and three-month follow-up. The pilot RCT will be followed by a process evaluation. For the process evaluation, stakeholders will be interviewed (N = 25), including 1) RCT participants, 2) PM + helpers, supervisors and trainers, 3) prison professionals, and 4) family members & friends of RCT participants. Data of the process evaluation will be analysed using reflexive thematic analysis. Discussion This pilot RCT will be the first to study the potential of WHO-developed scalable interventions aimed at reducing mental health problems within (Dutch) prisons. Results from this study could subsequently inform a potential full-powered RCT. Trial registration This trial is registered on ClinicalTrials.gov (number NCT05927987) on 13/06/2023.